Unveiling the Power of Burhānī Epistemology in Reshaping Islamic Economic Law for a Fair Financial Landscape - Mukhlishin, Mukhlishin; Wahyudi, Abdullah Tri; Ramadhan, Jelang (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2023)
This study aims to explain the concept of burhānī epistemology and its implementation in the development of Islamic economic law formulation. The method used in the research is a thematic literature review with qualitative approach based on empirical normative data to ensure the consistency of the research data. The result of this research is that burhānī epistemology as a logical method or argumentative rationale can be applied to the reality or context analysis of interest-based finance. The practice of imposing interest in the conventional financial system indicates an addition (ziyādah) that can harm one of the parties to the contract (baṭīl). In addition, the implementation of the burhānī method must include the bayānī method in the formulation of Islamic economic law because the reasoning process of the concept of interest must be linked to the concept of usury in the text (naṣ), which must be read and understood textually and contextually. The application of these findings is to review the reality of interest practices in the banking system as a home base in the formulation of Islamic economic laws by eliminating aspects of usury and interest in the financial system. The Burhani method is used to explain banking interest and contractual agreements that incorporate falsehoods like gharār (uncertainty) and injustice (mistreatment) against the parties.